1998
DOI: 10.1002/(sici)1097-0177(199806)212:2<214::aid-aja6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The mouseGtl2 gene is differentially expressed during embryonic development, encodes multiple alternatively spliced transcripts, and may act as an RNA

Abstract: We have isolated a novel mouse gene (Gtl2) from the site of a gene trap integration (Gtl2lacZ) that gave rise to developmentally regulated lacZ expression, and a dominant parental‐origin–dependent phenotype. Heterozygous Gtl2lacZ mice that inherited the transgene from the father showed a proportionate dwarfism phenotype, whereas the penetrance and expressivity of the phenotype was strongly reduced in Gtl2lacZ mice that inherited the transgene from the mother. Gtl2 expression is highly similar to the β‐galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 41 publications
4
118
2
Order By: Relevance
“…Finally, we have carried out a Northern hybridization analysis of RNA from a day-12.5 embryo using two different probes, one speci®c for the 5 H clone and another speci®c for the 3 H clone. The band patterns and fragment lengths observed were almost identical (data not shown) and the same as those shown in the report by SchusterGossler et al (Schuster-Gossler et al 1998).…”
Section: Structural Analysis Of the Meg3 And Gtl2 Genessupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, we have carried out a Northern hybridization analysis of RNA from a day-12.5 embryo using two different probes, one speci®c for the 5 H clone and another speci®c for the 3 H clone. The band patterns and fragment lengths observed were almost identical (data not shown) and the same as those shown in the report by SchusterGossler et al (Schuster-Gossler et al 1998).…”
Section: Structural Analysis Of the Meg3 And Gtl2 Genessupporting
confidence: 89%
“…Thus, it is possible that Meg3/ Gtl2 might function as an RNA. It has also been shown that long type transcripts are located in the nuclei of cells in the mouse (Schuster-Gossler et al 1998). However, as only short type transcripts were detected in the human brain, the importance of these long type transcripts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…11 Gtl2 probably acts as RNA transcript as no consensus sequence for translation was detected. 12 Dlk1 and Gtl2 are located within a 1 Mb imprinted cluster containing other imprinted genes such as the paternally expressed Dio3 gene, 13 a retrotransposon-like gene (Rtl1), 14 several maternally expressed non-coding RNAs, C/D small nucleolar RNAs 15 and numerous microRNAs (miRNAs). 14, 16 Paulsen et al 9 first identified a CpG-rich tandem repeat 'repeat area 1' in the intergenic (IG) region of Dlk1/Gtl2 that was conserved between mouse, human and sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, insertion of a transgene array between the IG-DMR and Meg3 promoter, when paternally inherited, prevents promoter methylation, leading to reactivation of the ncRNAs in cis and concomitant reduced expression of the protein-encoding genes. Insertion on the maternally inherited chromosome causes transcriptional interference with the Meg3 promoter and reciprocal gene mis-expression (Gtl2-LacZ mice Imprinting disorders affecting chromosome 14 (Schuster-Gossler et al 1996, Schuster-Gossler et al 1998, Sekita et al 2006, Steshina et al 2006, Fig. 2C).…”
Section: Regulatory Regionsmentioning
confidence: 99%
“…2C). Inheritance of a disrupted chromosome from the father mimics TS -with intrauterine growth restriction, relative macrocephaly and small placenta, failure to thrive in the early postnatal period with subsequent growth retardation into adulthood (Schuster-Gossler et al 1998, Charalambous et al 2014a. Maternal inheritance of the transgene insertion partially reproduces the gene expression pattern associated with Kagami-Ogata syndrome and causes placentomegaly, perinatal lethality and failed metabolic adaptations to postnatal life (Charalambous et al 2012).…”
Section: Mouse Chromosome 12 Uniparental Disomymentioning
confidence: 99%